Alte und neue Verlaufsformen im Deutschen - Eroms, Hans-Werner (Studia Germanica Posnaniensia, 2018)
In recent times, German as a language with a well-functioning tense system is developing a special progressive form, marking actions and processes which are continual and not yet terminated. There is a variety of forms like beim Arbeiten or gerade im Begriff sein zu arbeiten, but most usual and by far most grammaticalised is the am-progressive (er ist am Arbeiten, “he is working”). In this paper the restrictions which still exist are discussed. They are limited, but although they are not entirely accepted in standard German, the range of these constructions is extensive. In spite of this fact, the German language does not tend to develop general aspectual markers. A comparison with English shows this clearly. However, in its early periods the German language had overt aspectual characteristics. Especially constructions with the present participle and the auxiliary verbs sein and warden could function as aspect partners. These constructions gradually disappeared at the end of Middle High German. Thus, modern German has only very few aspectual markers, which are restricted to progressive constructions verbalizing actions and processes in actual situations.